Implementing mixed-criticality synchronous reactive programs upon uniprocessor platforms - Baruah, Sanjoy (Real-time systems, 2014)
Model-based design methodologies based on the synchrony assumption are widely used in many safety-critical application domains. The synchrony assumption asserts that actions (such as the execution of code) occur instantaneously; however, physical platforms obviously do not possess this property. This paper considers the problem of obtaining resource-efficient implementations of programs that are written under the synchrony assumption on actual platforms, such that these implementations execute in a manner that is semantically consistent with the execution sequences that would occur if the synchrony assumption were to hold.